(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Clinical trials for human use have the purpose to verify the effectiveness and the security of new pharmaceutical products on human beans. This scientific process represents a fundamental step on the development of the medical science and of the human health, but the necessary human participation has determined the need to provide for a legal regulation of all the aspects of these clinical trials. This paper aims at describing some legal aspects of the clinical trials regulation, focusing on the new European legislation: The Regulation (EU) No 536/2014. Through the analysis of the most controversial issues in the clinical trials regulation (the public access to clinical information and the Ethics Committee’s role in the assessment of the trial protocol), it’s possible to evaluate the main innovations and the effects produced by the new Regulation to make the clinical trials legislation more uniform in the EU territory.